2021
DOI: 10.1186/s12912-021-00662-8
|View full text |Cite
|
Sign up to set email alerts
|

Does heavy mental workload affect moral sensitivity among critical care unit nursing professionals? a cross-sectional study

Abstract: Background Moral sensitivity creates the basic attitude in providing effective ethical care to patients. Heavy mental workload is a major concern of critical care nursing professionals, which could adversely affect nursing staff and patients. The present study aimed to investigate the effects of mental workload and some demographic variables on the moral sensitivity of critical care nursing professionals. Methods This cross-sectional, descriptive-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The present study found a moderate level of moral sensitivity in nurses caring for elderly COVID-19 patients; in another study, the same results were obtained [ 23 ]. While another study reported a high range of moral sensitivity in critical care nursing professionals [ 29 ]. This difference can be due to differences in care units (critical care unit vs. general ward).…”
Section: Discussionmentioning
confidence: 99%
“…The present study found a moderate level of moral sensitivity in nurses caring for elderly COVID-19 patients; in another study, the same results were obtained [ 23 ]. While another study reported a high range of moral sensitivity in critical care nursing professionals [ 29 ]. This difference can be due to differences in care units (critical care unit vs. general ward).…”
Section: Discussionmentioning
confidence: 99%
“…Te validity and reliability of this questionnaire have been confrmed in previous studies in critical care settings [30]. Te reliability of the Farsi version of this questionnaire was confrmed by Hariri et al with a Cronbach's alpha of 75% [31] and another study in critical care settings [32].…”
Section: Data Collectionmentioning
confidence: 90%
“…In addition, it has been shown that nurses are always committed to the principles of their professional ethics in the most difficult situations. The study of Zahednezhad et al (2021) showed that although nurses have a high workload, this does not reduce their moral sensitivity.…”
Section: Discussionmentioning
confidence: 99%